Factors influencing job motivation among Malaysian police officers in the Perlis contingent - Noor Alyzamleana, Aladin (2020)
The main objective of this study is to examine factors that influence job motivation among Malaysian police officers in the Perlis Contingent. There are three variables that have been used in this study to examine the relationship with job motivation which is leadership style, rewards and recognition and training and development. The samples of this study consist of 134 police officers from rank and file officers to senior officers in Perlis Contingent. The data were analysed using the software SPSS version 25.0.The data were collected through the distribution of surveys using questionnaires. A few analysis has been made such as reliability analysis, normality analysis, descriptive analysis, correlation analysis (Pearson correlation analysis) and regression analysis. Overall results from Pearson correlation analysis showed there is a relationship between the variable leadership styles, recognition and rewards, training and development and job motivation. However, not all variables have a significant correlation. By processing another step using multiple regressions, (leadership style and training and development) are the independent variables that have the greatest influence on dependent variables (job motivation). However, another one independent variables (reward and recognition) were not significant to affect job motivation. The result of this study showed that leadership style and training and development factors play an important role to influence job motivation, while rewards and recognition do not have a significant relationship with job motivation, among police officers at Perlis Contingent.